Cholesterol loading suppresses the atheroinflammatory gene polarization of human macrophages induced by colony stimulating factors - Jani Lappalainen (Nature Portfolio, 2021)
Abstract In atherosclerotic lesions, blood-derived monocytes differentiate into distinct macrophage subpopulations, and further into cholesterol-filled foam cells under a complex milieu of cytokines, which also contains macrophage-colony stimulating factor (M-CSF) and granulocyte–macrophage-colony stimulating factor (GM-CSF). Here we generated human macrophages in the presence of either M-CSF or GM-CSF to obtain M-MØ and GM-MØ, respectively. The macrophages were converted into cholesterol-loaded foam cells by incubating them with acetyl-LDL, and their atheroinflammatory gene expression profiles were then assessed. Compared with GM-MØ, the M-MØ expressed higher levels of CD36, SRA1, and ACAT1, and also exhibited a greater ability to take up acetyl-LDL, esterify cholesterol, and become converted to foam cells. M-MØ foam cells expressed higher levels of ABCA1 and ABCG1, and, correspondingly, exhibited higher rates of cholesterol efflux to apoA-I and HDL2. Cholesterol loading of M-MØ strongly suppressed the high baseline expression of CCL2, whereas in GM-MØ the low baseline expression CCL2 remained unchanged during cholesterol loading. The expression of TNFA, IL1B, and CXCL8 were reduced in LPS-activated macrophage foam cells of either subtype. In summary, cholesterol loading converged the CSF-dependent expression of key genes related to intracellular cholesterol balance and inflammation. These findings suggest that transformation of CSF-polarized macrophages into foam cells may reduce their atheroinflammatory potential in atherogenesis.